Neuroimaging Studies in Patients With Mental Disorder and Co-occurring Substance Use Disorder: Summary of Findings - Stoychev, Kaloyan Rumenov (Frontiers in Psychiatry, 2019)
Introduction: more than half of psychiatric patients have comorbid substance use disorder (dual diagnosis) and this rate, confirmed in many epidemiological studies, is far bigger compared to general population. Combined operation of self-medication mechanisms, common etiological factors and mutually causative influences most likely accounts for comorbidity which, despite its clinical prevalence, remains underrepresented in psychiatric research, especially in terms of neuroimaging. The current paper attempts to review and discuss all published methodologically sustainable structural and functional neuroimaging studies in comorbid subjects published in the last twenty years. Methods: performing a systematic PubMed/MEDLINE, Web of Science and Cochrane databases search with predefined key-words and selection criteria, 43 structural and functional neuroimaging studies were analyzed. Results: although markedly inconsistent and confounded by a variety of sources, available data suggest that structural brain changes are slightly more pronounced, yet not qualitatively different in comorbid patients compared to non-comorbid ones. In schizophrenia (SZ) patients, somewhat greater grey matter reduction is seen in cingulate cortex, dorsolateral prefrontal and frontotemporal cortex, limbic structures (hippocampus) and basal ganglia (striatum). The magnitude of structural changes is positively correlated to duration and severity of substance use, but it is important to note that at least in the beginning of the disease, dual diagnosis subjects tend to show less brain abnormalities and better cognitive functioning than pure SZ ones suggesting lower preexisting neuropathological burden. When comparing neuroimaging findings in SZ and bipolar disorder subjects, dorsolateral prefrontal, cingular and insular cortex emerge as common affected areas in both groups which may indicate a shared endophenotypic (i.e. transdiagnostic) disruption of brain networks involved in executive functioning, emotional processing and social cognition which renders affected individuals susceptible to both mental disorder and substance misuse. In patients with anxiety disorders and substance misuse, a common neuroimaging finding is reduced volume of limbic structures (n. accumbens, hippocampus, amygdala). Whether this is a neuropathological marker of common predisposition to specific behavioral symptoms and drug addiction or a result from neuroadaptation changes secondary to substance misuse is unknown. Future neuroimaging studies with larger samples, longitudinal design and genetic subtyping are warranted to enhance current knowledge on comorbidity.